Prophetic values in the leadership of Muhammadiyah Yogyakarta school - Dewantoro, Mohammad Hajar; Susilo, Mohamad Joko (Journal of Education and Learning (EduLearn), 2025)
Rasulullah SAW was successful in becoming a uswatun hasanah (good leader and role model). This field research aims to determine the prophetic values in leadership of Yogyakarta Muhammadiyah schools and percentage of their implementation. Research was carried out with a purposive technique in primary and secondary education Muhamamdiyah schools in Yogyakarta, with the subject being the principal. The data collection techniques used questionnaires, interviews, and documentation, while the data analysis technique was carried out descriptively qualitatively. The results showed that prophetic values in Muhammadiyah school leadership in Yogyakarta found four main values that exist in all Muhammadiyah schools: i) adopting a collegial collective leadership system; ii) based on faith; iii) oriented towards the quality of progressing schools; and iv) applying ta'awun (cooperation). The highest percentage of implementation of prophetic values based on 3 aspects (humanization, liberation, and transcendence) was found at Muhammadiyah Elementary School Condongcatur and Muhammadiyah Vocational School Pakem at 92.9%.